The Empowerment of Micro, Small Medium Enterprises (MSMEs) Bussiness Through Productive Zakat as an Effort to Alleviate Poverty and Unemployment in Indonesia - Nuarisa, Risma Hafida; Aziz, Muhammad Abdul; Retnowati, May Shinta (Journal of Economics, Bussiness and Management Issues, 2024)
Indonesia become a country with the largest Muslim population in the world in 2022. This is in line with the number of MSMEs in Indonesia. MSMEs have a major role in economic growth and reducing poverty in Indonesia. So MSMEs become the biggest contribution to poverty alleviation and employment in Indonesia. Therefore productive zakat is an appropriate, alternative and profitable instrument for developing MSMEs as well as breaking the cycle of poverty and unemployment in Indonesia.  The purpose of this study is to determine the potential of productive zakat in empowering MSMEs businesses to alleviate poverty and unemployment in Indonesia. This research is a descriptive qualitative research by describing that zakat productive MSME businesses are able to alleviate poverty and absorb labor. The data sources used are primary data and secondary data. The data collection technique used is library research (library research), namely collecting or compiling data by using written materials regarding productive zakat and MSMEs. The results of this reserch is show that the presence of productive zakat is able to overcome the constraints on the lack of capital faced by MSMEs. This is supported by the large number of Muslim communities in Indonesia. MSMEs empowerment is carried out by providing assistance and coaching to help people with low education in developing their knowledge and skills.  Then, it is hoped that it can help alleviate poverty and absorb labor so that it can increase economic growth in Indonesia.